Analysis of Permeability and Compressive Strength of Local Sand of West Kotawaringan District as Molding Sand in Metal Casting - Aspiyansyah, Aspiyansyah; Harianto, Agus; Mustofa, Edi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
Sand is the most widely used material as a molding material in the metal casting process. Sand can be used as a molding medium if it meets the requirements, including good formability and good permeability. This research was conducted by examining West Kotawaringin local sand by providing several tests, which include a clay content test, a water content test, a formability test, and a permeability test. The test results for local sand showed that the permeability value of sand was 0.001-0.032 cm/sec and the compressive strength value of sand was 0.073-0.126 kg/cm2. These results show that the local sand of West Kotawaringin meets the requirements of molding sand so that it can be used as molding sand in metal casting.